Inhibitory activity of Varronia curassavica and Mikania laevigata fractions against pathogens associated with persistent dental infections - Loiane Massunari; Amanda C A Souza; Paula F Kreling; Juhan A Scardelato; Luis V. S. Sacramento; Eloi Dezan Jr; Cristiane Duque (São Paulo State University (UNESP), 2020)
Herbal medicines have been studied and potential antimicrobial agents emerging as treatment against oral diseases. This study evaluated the antimicrobial activity of the Mikania laevigata (ML) and Cordia verbenacea (CV) crude extract and fractions against oral pathogens associated with persistent dental root infections, under planktonic and biofilm conditions. Minimal inhibitory concentrations and minimal bactericidal/fungicidal concentrations were determined for the ML and CV fractions/extracts against Enterococcus faecalis, Actinomyces israelii, Pseudomonas aeruginosa and Candida albicans using the microdilution method. The best results were chosen for subsequent biofilm assays. All tested ML and CV extracts/fractions had inhibitory activity against E. faecalis and A. israelii. ML ethyl acetate fraction affected the growth of all microorganisms tested. C. albicans and P. aeruginosa were not affected by any CV extract/fraction. ML ethyl acetate fraction eliminated E. faecalis, A. israelii and P. aeruginosa biofilms after 24h. Similar result was observed for ML crude hydroethanolic extract and its hexane fraction for A. israelii. CV hexane fraction was able to eliminate A. israelli biofilms. None of the tested extracts or fractions eliminated C. albicans biofilm. Mikania laevigata ethyl acetate fraction is an efficient antimicrobial agent against oral pathogens and could be indicated for the treatment of persistent dental infections.